School Committee in Providing Support to Madrasah Aliyah Negeri 2 Jember - Nofiyanata, Dwi; Usriyah, Lailatul (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
The school committee is an independent body that helps and becomes a school partner. This position is very strategic for developing the quality of education in an institution. The school committee also contributes to developing the quality of education at MAN 2 Jember. This research was conducted at MAN 2 Jember. This study aims to: (1) Describe the role of the school committee in providing considerations to develop the quality of education in MAN 2 Jember. (2) Describe the School Committee in providing support to MAN 2 Jember. This study uses qualitative methods and descriptive research types. Determination of research subjects using purposive sampling. Data collection techniques using observation, interviews, and documentation. Data analysis uses the Miles and Huberman model, they are data condensation, data presentation, drawing conclusions. The validity of the data using source triangulation and technique triangulation. The results of this study are: (1) The school committee as an advisory body provides input and ideas to schools regarding programs at school either through formal or informal meetings. The school committee also provides input regarding school facilities and infrastructure as well as program budgeting funded by the school committee. The budget in question is that which is not funded by the government and schools. The school committee will not approve a program when it is deemed to be of little use or makes parents object. (2) The school committee as a supporting body in MAN 2 Jember is characterized by its active role in supporting programs determined by the school and participating in solving problems that occur in schools. The school committee also contributes to realizing good quality education. The MAN 2 Jember Committee also supports the completeness of madrasah facilities and infrastructure in the form of personnel, materials, and thoughts.